Histamine-forming ability of Lentilactobacillus parabuchneri in reduced salt Cheddar cheese. (September 2021) - de A. Møller, Cleide O.; Castro-Mejía, Josué L.; Krych, Lukasz; Rattray, Fergal P.
Abstract: Lentilactobacillus parabuchneri, a member of the non-starter microbiota in cheese, was recently associated with fast and effective histamine-formation ability, a safety issue. The present study was performed to investigate Lentilactobacillus parabuchneri KUH8, a histamine-producer (HP) in reduced-salt Cheddar cheese. Four cheeses were manufactured: 1) normal-salt (NS); 2) reduced-salt (RS); 3) normal-salt with HP (NS+HP); 4) reduced-salt with HP (RS+HP). Two replicates were produced with milk from the same batch, and the cheeses ripened at 10 and 15 °C. Cheeses were sampled immediately after manufacture and after 1, 3 and 6 months of ripening. Ultra-high-performance-liquid chromatography indicated that with the HP, histamine reached higher levels in reduced-salt cheeses (3.5–3.7% S/M) at 15 °C (86, 1112, 2149 and 3149 mg kg −1 ), compared to normal-salt cheeses (5.4–6.3% S/M) at 10 °C (78, 584, 593 and 1389 mg kg −1 ), at each respective cheese-sampling point. Higher salt-content reduced the growth rate of non-starter microbiota, but after six months the levels in all cheeses were similar, according to the ripening temperature: at 10 °C (8.05–8.30 log10  cfu g −1 ), and at 15 °C (6.00–6.94 log10  cfu g −1 ). A correlation between increased histamine levels, non-starter-cell development and pH was found. This study highlights the importance of normal-salt content and low-ripening temperature as measures to control histamine-formation and to improve safety in cheese. Highlights: The histamine producer L. parabuchneri KUH8 was tested in reduced-salt Cheddar cheese (3.5–3.7% S/M). The histamine formation was monitored during six months of ripening at 10 and 15 °C. Normal salt content (5.4–6.3% S/M) limits the histamine formation at low temperature. In reduced salt cheeses high levels of histamine (1389–3149 mg kg −1 ) were formed, especially at 15 °C. To improve safety in cheese: Use of normal salt content and low ripening temperature.